2019
DOI: 10.1002/jcc.25776
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of aminotriethylene glycol functionalized single wall carbon nanotubes: A density functional based tight binding molecular dynamics study

Abstract: Pristine CNTs are exemplary hydrophobic solutes; properly functionalized CNTs can be seen as hydrophilic ones. The solubility of aminotriethylene glycol (ATG) functionalized single walled carbon nanotubes (fSWCNTs) were examined using density functional based tight binding method. According to the dynamics study, the ATG-fSWCNTs interaction energies (IE) and diffusion coefficients (D) are diameter dependent. As the diameter of the (n,0) tube is incrementally increased, a distinguishable pattern is observed, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…BNNTs are indeed not conductive irrespective of their morphological properties, 6,7 whereas CNTs are conductive and show band gap changes with the change in the nanotube diameter size. 8 Several nanostructured h-BN compounds with a lattice characterized by the hexagonal symmetry have been synthesized: nanosheets, 9,10 nanocones, 11 nanotubes, 12 nanohorns, 13 and nanorods 14 as well as several nanostructured objects, collectively named nanoflakes.…”
Section: Introductionmentioning
confidence: 99%
“…BNNTs are indeed not conductive irrespective of their morphological properties, 6,7 whereas CNTs are conductive and show band gap changes with the change in the nanotube diameter size. 8 Several nanostructured h-BN compounds with a lattice characterized by the hexagonal symmetry have been synthesized: nanosheets, 9,10 nanocones, 11 nanotubes, 12 nanohorns, 13 and nanorods 14 as well as several nanostructured objects, collectively named nanoflakes.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation‐fitting def2‐TZVPP/C auxiliary basis set is used, along with the coulomb‐fitting def2/J basis set, to accelerate the DLPNO‐CCSD(T) calculations. For solvent corrections to coupled cluster electronic energies, the conductor‐like polarized continuum model (CPCM) (dielectric constant = 36.6, refractive index = 1.344 for acetonitrile) [ 26 ] as implemented in ORCA 4.1 [ 27 ] is utilized. Thermal (Temperature = 298.15 K) and nonthermal corrections were obtained from B3LYP frequency calculations.…”
Section: Methodsmentioning
confidence: 99%
“…And graphenes with LD are semiconductors with a reduced band gap. , In our previous investigation, the electronic and mechanical properties of graphene with LD consisting of squares and octagons have been predicted . The LD could introduce defective states in the original forbidden band gap. , And the valance band maximum (VBM) and the conduction band minimum (CBM), which are usually relative to the chemical active sites, are also transferred from the edge sites to the LD atoms. When the TM atoms adsorb on graphene, they intend to adsorb at these defective sites with high chemical active properties of the graphene. ,, Salmeron found that water could split graphene and intercalates . Cheng investigated single TM atom adsorption on graphene. Researchers have only recently focused on the single TM atom adsorption on graphene sheet in their work, but the topological, structural, magnetic, and electronic properties of the TM atom adsorption on graphene are still unknown.…”
Section: Introductionmentioning
confidence: 99%